Financial Statement Model Based on SAK EMKM In The “Polife” Student Entrepreneur Group - Lusye Corvanty Kumaat; Yelly Sjenny Paendong; Jerry Sonny Lintong (Future Science, 2021)
The purpose of this research is to create a Financial Report Model based on SAK-EMKM in the Student Entrepreneurial Group